Diagnostic accuracy of capsule endoscopy compared with colonoscopy for polyp detection: systematic review and meta-analyses - Kjølhede, Tue; Ølholm, Anne Mette; Kaalby, Lasse; Kidholm, Kristian; Qvist, Niels; Baatrup, Gunnar (Endoscopy, 2020)
Background Colon capsule endoscopy (CCE) is a technology that might contribute to colorectal cancer (CRC) screening programs as a filter test between fecal immunochemical testing and standard colonoscopy. The aim was to systematically review the literature for studies investigating the diagnostic yield of second-generation CCE compared with standard colonoscopy.Methods A systematic literature search was performed in PubMed, Embase, and Web of Science. Study characteristics including quality of bowel preparation and completeness of CCE transits were extracted. Per-patient sensitivity and specificity were extracted for polyps (any size, ≥ 10 mm, ≥ 6 mm) and lesion characteristics. Meta-analyses of diagnostic yield were performed.Results The literature search revealed 1077 unique papers and 12 studies were included. Studies involved a total of 2199 patients, of whom 1898 were included in analyses. The rate of patients with adequate bowel preparation varied from 40 % to 100 %. The rates of complete CCE transit varied from 57 % to 100 %. Our meta-analyses demonstrated that mean (95 % confidence interval) sensitivity, specificity, and diagnostic odds ratio were: 0.85 (0.73–0.92), 0.85 (0.70–0.93), and 30.5 (16.2–57.2), respectively, for polyps of any size; 0.87 (0.82–0.90), 0.95 (0.92–0.97), and 136.0 (70.6–262.1), respectively, for polyps ≥ 10 mm; and 0.87 (0.83–0.90), 0.88 (0.75–0.95), and 51.1 (19.8–131.8), respectively, for polyps ≥ 6 mm. No serious adverse events were reported for CCE.Conclusion CCE had high sensitivity and specificity for per-patient polyps compared with standard colonoscopy However, the relatively high rate of incomplete investigations limits the application of CCE in a CRC screening setting.